Pemberdayaan Santri TPA Berbasis Kaderisasi - Desy Sopia Fitria; Eka Kurniati; Reyhan Arifqi Khalqi; Ahmad Syarifin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research is motivated by observation data that shows the problems that exist in the TPA Al-Iman mosque, Pagar Jati village, many students who are not right in reading the verses of the Qur'an but are still allowed to continue to a higher level of study. and another problem is the lack of teaching staff for students at TPA Hidayatul Istiqomah 2. This study aims to obtain prospective candidates or potential cadres from existing students and a description of the implementation of cadre-based learning at the TPA Al-Iman mosque, Pagar Jati village, Semidang Lagan District, Central Bengkulu. Cadre formation itself is a form of sustainable leadership in order to continue future leadership. The function of this cadre formation is to prepare prospective leaders in the future. Based on the results of the community service that has been carried out, it was found that there were 12 prospective cadres who were selected and would receive guidance from the devotees whose knowledge would be channeled back to other students. And seen from the end of the service activities and the absence of mentoring from the devotees, they gave a response that they had high enthusiasm to become the successors of the previous teachers so that the prospective cadres who had been determined and mentored still continued their religious study activities at the TPA even after the devotion activities of the devotees were finished.